Helical double and triple walled carbon nanotubes from combustion catalyst by chemical vapour deposition techniques - S. ARULARASI; T. SOMANATHAN (International Journal of Pharma and Bio Sciences, 2017)
A simple route for the synthesis of helical double walled carbon nanotubes (DWCNTs) and triple walled carbon nanotubes (TWCNTs) by chemical vapour deposition of acetylene on Cr0.1Ni0.3Mg0.6O catalyst. In this study, high-quality helical double and triple helix carbon nanotubes have been synthesized on combustion catalyst. The morphologies and qualities of the CNTs were characterized by x-ray diffraction scanning electron microscope, transmission electron microscope, and Raman spectroscopy. Structural control over the hDWCNTs and hTWCNTs was achieved by simply altering the catalyst composition, reaction temperatures and acetylene flow rates. This study demonstrates that Cr can act as an efficient catalyst for the growth of hDWCNTs and hTWCNTs. This technique opens up the possibility for economically preparing CNTs with controlled coiled structure.